Understanding the pulsed laser-induced modification processes of TiO2 nanomaterials in aqueous solution - An, Hee Jun; Carl, Nkenku; Yoo, Youngdong; Kang, Hyuk; Kim, Yu Kwon (Bulletin of the Korean Chemical Society, 2023)
Three different types of TiO2 nanoparticles in anatase and rutile phases were subject to nanosecond 532-nm laser pulses in aqueous solution for enhanced reactivity in photocatalytic applications. Color changes observed during the laser processes resulted from laser pulse-induced heating of TiO2 surfaces to form surface disorder with surface defects. Interestingly, TiO2 nanoparticles with different size and bulk phases undergo different changes in surface morphology, bulk phase, and defect density under the same laser pulses. The results are related with the differences in the absorption by initial defects on the TiO2 surface. Our results show that the type and density of initial defects within TiO2 matrix are important in determining subsequent thermal equilibrium-driven changes. It is suggested that nanosecond laser pulses with energies lower than the bandgap of the semiconductor materials provide a chance for selective modification of oxide nanomaterials such as TiO2 for a new photoresponsive functionality in diverse applications.
Keywords: Anatase phasis; Bulk phase; Initial defects; Laser induced; Laser induced modification; Modification process; Pulsed laser-induced process; Rutile phase; Surface-modification; TiO2 nanoparticle; photocatalysis; pulsed laser-induced processes; surface defects; surface modification; TiO2 nanoparticles